Co-pyrolysis characteristics of waste tire and maize stalk using TGA, FTIR and Py-GC/MS analysis. (1st April 2023) - Wang, Zhiwei; Wu, Mengge; Chen, Gaofeng; Zhang, Mengju; Sun, Tanglei; Burra, Kiran G.; Guo, Shuaihua; Chen, Yan; Yang, Shuhua; Li, Zaifeng; Lei, Tingzhou; Gupta, Ashwani K.
Highlights: Co-pyrolysis of waste tire and maize stalk were investigated using TGA, FTIR and Py-GC/MS. Synergy was observed in co-pyrolysis from increased weight loss. FTIR results showed that the waste tire and maize stalk had similar functional groups. PAHs were inhibited but hydrocarbons and alcohols were improved during co-pyrolysis. Abstract: Co-pyrolysis technology is an important pathway to realize efficient utilization of waste tires and biomass resources, solve environmental problems and help mitigate the energy supply issues. Results are presented on the pyrolysis behavior of waste tire, maize stalk and their mixtures using thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, and gas chromatography/mass spectrometry (GC/MS). The results showed synergistic effects in the co-pyrolysis of waste tire and maize stalk. The co-pyrolysis results showed increased weight loss. The pyrolysis of waste tire and maize stalk was relatively independent in the co-pyrolysis process. The FTIR results showed that the waste tire and maize stalk had similar functional groups, and that the co-pyrolysis products not only included ketones, aldehydes and acids, but also H2 O and SO2 . The GC/MS analysis data showed that co-pyrolysis helps to inhibit polycyclic aromatic hydrocarbons (PAHs) production and improve products yield of hydrocarbons and alcohols. The results presented here provide a fundamental basis of the co-pyrolysis technology for the disposal of waste tire and agricultural biomass for cleaner energy conversion and greener environment.